Music Creativity In The Brascong Vijaya Kusuma Keroncong (Jurnal Seni Musik, 2022)
Creativity in music can be formed by observing, studying, and understanding existing creative works or creating new music. In the city of Salatiga, there is a keroncong orchestra called "Brascong Vijaya Kusuma." This study aimed to determine, analyze, and describe the musical creativity in the brascong keroncong orchestra Vijaya Kusuma in Salatiga. The method used in this study is a qualitative research method that presents a descriptive analysis. This research approach uses musicology. The results of this study indicated that creativity in brascong keroncong Orchestra Vijaya Kusuma transpired because of the encouragement of Ajenrem 073 Salatiga, which, indeed, Brascong has the task of providing entertainment to the soldiers in Ajenrem 073 Salatiga. Musical creativity that exists in brascong Orchestra keroncong Vijaya Kusuma includes: (1) the arrangement of the addition of wind instruments such as trumpet, tenor horn, and trombone into keroncong music inspired by the Corsican in unit Ajenrem 073 Salatiga; (2) the creation of the song "Kr. Tanah Airku" did not use flute/violin prospels instead uses trumpet instruments; (3) in the interlude, brass instruments play blocking notes and play imitations of the main melody; (4) in the coda brass instruments play passing notes and blocking notes and at the end get ritardando;(5) the use of chords in the arrangement of the song "Kr. Tanah Airku" added a chord outside the original keroncong standard chord. Kreativtas music in brascong through the stages of creativity which consist of; aspects of personality, drivers, processes, and products.